THE EUROPEAN UNION, THE UNITED STATES, AND THE GENETICALLY MODIFIED ORGANISMS (GMOs) - Anisa; Chelsilya; Grace Yohana; Mucco Eva; Morry Zefanya; Nadila (Sociae Polites, 2020)
Current technological advances have been present in all aspects of human life, including technological advances in biotechnology. Biotechnology not only raises hope for science but also raises heated debates among scientists, especially between the European Union and the US. This debate arises because of differences in perspective between the EU and the US. The EU has stringent rules regarding the development efforts of genetically modified organisms (GMOs). At the same time, the US thinks that GMOs are part of agriculture, so there is no need for any special laws to regulate them. Various side effects also come hand in hand with the birth of GMOs. They are ranging from adverse effects on human health, the health of food products, and even environmental damage. The development of GMOs can damage the ecosystem of species that exist in the environment. Still, more complex problems arise due to GMOs like economic problems and monopolies. Keywords: The GMOs, The EU, The US.